Encontros na Península, de Milton Hatoum: Um diálogo com A causa secreta, de Machado de Assis / Encontros na Península, by Milton Hatoum: A dialogue with the Secret Cause, by Machado de Assis - Ataíde, Maria Betânia da Costa; Amorim, José Edilson de (ID on line. Revista de psicologia, 2021)
Resumo: Nesse artigo temos como objetivo apresentar uma leitura comparada do conto “Encontros na Península”, de Milton Hatoum com “A causa secreta”, de Machado de Assis. Ao longo do trabalho apresentamos algumas reflexões em torno da pergunta da personagem Victoria Soller. Teoricamente nos baseamos em Carvalhal (2004) com a obra Literatura Comparada, e em Bakhtin Dialogismo e Polifonia (2016). Notamos através das relações intertextuais que o conto “Encontros na Península” dialoga com alguns textos machadianos. Palavras-chave: Machado de Assis; Milton Hatoum; Literatura comparada. Abstract: In this article we aim to present a comparative reading of the short story “Encontros na Península”, by Milton Hatoum with “A causa secreta”, by Machado de Assis. Throughout the work, we present some reflections on the question of the character Victoria Soller. Theoretically, we are based on Carvalhal (2004) with the book Comparative Literature, and on Bakhtin Dialogismo e Polifonia (2016). Through the intertextual relationships, we noticed that the short story “Encontros na Península” dialogues with some Machadian texts. Keywords: Machado de Assis; Milton Hatoum; Comparative literature.